PENYULUHAN PEMBUATAN DAN PENGGUNAAN ALAT PEMOTONG RUMPUT SEDERHANA DI DESA SENDANG LAOK MADURA (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
Community empowerment through the development of the local potential of simple grass cutter as a work tool for the residents of Sendang Laok Village, Madura. We are KKN UNTAG SURABAYA 2018 The TTG Division shares knowledge regarding the making and use of simple lawn mowers so that it can be applied to the activities of daily life of the villagers. Making simple lawn mowers is very easy and does not require a lot of money. Many of the outcomes that we produce from this simple Grass Cutting tool work program, namely: tools, tool making modules, tool maintenance modules, design works, prototype models and questionnaire social engineering that are occupied by residents before and after counseling found an increase in the percentage of related citizen knowledge a simple lawn mower of 40.4%, of which NEUTRAL knowledge becomes VERY KNOWLEDGE.